Experimental investigation for optical flatness in an aluminium alloy 6061 by single point diamond turning - Surya Prabhu Mohanasundaram. (2013)
Optically flat components are increasing in more demand, which is hard to manufacture with high precision and accuracy. Ultra precision (SPOT) Single Point